2021
DOI: 10.3390/plants10020259
|View full text |Cite
|
Sign up to set email alerts
|

Drought Stress Impacts on Plants and Different Approaches to Alleviate Its Adverse Effects

Abstract: Drought stress, being the inevitable factor that exists in various environments without recognizing borders and no clear warning thereby hampering plant biomass production, quality, and energy. It is the key important environmental stress that occurs due to temperature dynamics, light intensity, and low rainfall. Despite this, its cumulative, not obvious impact and multidimensional nature severely affects the plant morphological, physiological, biochemical and molecular attributes with adverse impact on photos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
562
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 970 publications
(585 citation statements)
references
References 248 publications
(215 reference statements)
14
562
1
8
Order By: Relevance
“…Soil salinity severely affects crop growth and yield, particularly in arid and semiarid areas of the world [126,127]. Globally, salt-affected areas occupied 1 billion ha, and it is estimated that this area will further expand due to global climate change and poor land and water resources management [128].…”
Section: Impact Of Biochar On Salt-affected Soilsmentioning
confidence: 99%
“…Soil salinity severely affects crop growth and yield, particularly in arid and semiarid areas of the world [126,127]. Globally, salt-affected areas occupied 1 billion ha, and it is estimated that this area will further expand due to global climate change and poor land and water resources management [128].…”
Section: Impact Of Biochar On Salt-affected Soilsmentioning
confidence: 99%
“…These processes may include all biological processes in stressful plants such as leaf photosynthesis (Fan et al 2020), metabolism of pollens (Nischal and Sharma 2020), and nearly all processes. The biochemical traits may include the antioxidant defense system and enzymes, whereas the physiological parameters may include all physiological processes like photosynthesis and the morphological features involve all features linked to the shape of plant organs like leaves, stems, and roots (Seleiman et al 2021). The anatomical features are still needed to be investigated in stressful plants.…”
Section: Changes In Cultivated Plants Under Stressmentioning
confidence: 99%
“…Cultivated plants face generally during their growth environmental stresses including abiotic and biotic stress (El-Ramady et al 2019). These stresses include drought, salinity (Akcin et al 2017), waterlogging Tian et al 2021), high or low temperatures, high or low light, flooding, deficient or excess nutrients (Adejumo et al 2020) and heavy metals (Abdalla et al 2020;Stavridou et al 2021;Seleiman et al 2021). Several studies have been focused on the single or individual stress as a simple study but recently increasing concerns on combined stress have reported like drought and heat stress (Duc et al 2018;Parvathi et al 2020;Li et al 2021;Stavridou et al 2021), salinity and heat stress (Bayoumi et al 2021;Shalaby et al 2021), salinity and nutrient stress (Chrysargyris et al 2019;Pandey et al 2019), drought and pathogen infection (Dixit et al 2019;Gupta et al 2020), drought and element stress (Naz et al 2021), salinity and waterlogging stress (Duan et al 2018;Gill et al 2019;Cheng et al 2021), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to reduced photosynthesis after anthesis, current photosynthetic assimilates reduced, gradually affecting the grain filling [16]. Severe environmental stress may reduce grain filling, leaf desiccation, and reduced photosynthesis [17][18][19]. Genotypes with the ability to mobilize the stem reserve under stress conditions are likely to yield better [13].…”
Section: Introductionmentioning
confidence: 99%